Fusion PSPnet Image Segmentation Based Method for Multi-Focus Image Fusion - Jingchun Zhou; Mingliang Hao; Dehuan Zhang; Peiyu Zou; Weishi Zhang (IEEE Photonics Journal)
To address the problem that the traditional multi-focus images fusion methods cannot fully use of spatial context information. A novel image segmentation method for multi-focus image fusion is proposed. This method consists of two main steps, using PSPnet combined, and the region optimization using ConvCRFs for multi-focus image fusion. PSPnet is utilized to extract the focused region of the source image, and ConvCRFs is used to optimize the segmentation map to obtain a refined map. Finally, 20 couples of color multi-focus images are employed as experimental datasets, and the contrast results show that the proposed method has a better fusion visual effect than the other state-of-the-art in subjective and objective point of view.